Giant and Tunable Optical Nonlinearity in Single-Crystalline 2D Perovskites due to Excitonic and Plasma Effects - Abdelwahab, Ibrahim (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.